The Role of the Subdistrict Head in the Development of the Red and White Village Cooperative in Nagrak, Sukabumi Regency - Ening Lasminingsih; Hardiyanto Rahman (INFOKUM, 2026)
This research was motivated by the lack of knowledge and understanding among the administrators and members of the Red and White Village Cooperative regarding the development of business types and the utilization of village potential. The purpose of this study was to analyze and examine the role of the Subdistrict Head (Camat) in providing guidance to the Red and White Village Cooperative. The study employed a descriptive qualitative method. The data sources consisted of primary and secondary data. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study indicate that the role of the Camat in the Red and White Village Cooperative is crucial as a facilitator, advisor, and supervisor at the regional level. The Camat of Nagrak has carried out a strategic role as the main facilitator and institutional mobilizer through concrete activities such as socialization programs, monitoring of Special Village Deliberation Meetings (Musdesus), assistance with legal documentation (Notarial Deeds), and monitoring of business initiatives. These measures demonstrate that the Camat is not only focused on the legal aspects of cooperative establishment but also encourages the cooperative’s function as an independent and productive pillar of the village economy. Thus, the implementation of the Camat’s role can generally be considered adequate and has shown positive results during the initial stages and legal administration process. However, to ensure sustainability and optimize its impact, this role still requires strengthening and continuous guidance. Such optimization should focus on overcoming internal challenges, particularly the limitations of human resources both at the subdistrict and village levels, as well as strengthening coordination mechanisms among stakeholders.